Influence of counterions on the formation of supramolecular platinum group metal complexes containing pyridyl thioamide derivatives: antioxidant and antimicrobial studies. (29th September 2022) - Dkhar, Lincoln; Gupta, Hrishikesh; Poluri, Krishna Mohan; Gannon, Paige M.; Kaminsky, Werner; Kollipara, Mohan Rao
Abstract : A series of half-sandwich metal thioamide derivative complexes exhibiting interesting coordination modes in the presence of counterions. Abstract : A series of ruthenium, rhodium and iridium complexes containing thioamide derivatives have been synthesized. In the presence of a counterion (NH4 PF6 ) binuclear complexes were isolated, whereas in the absence of a counterion mononuclear complexes were obtained. The binuclear complexes exist as supramolecular structures by bridging the two metal centers through nitrogen and sulfur atoms of the two ligands. The antibacterial activity of most of the tested compounds was found to be potent, especially towards Gram-positive bacteria.